Webtoon Pupus Dropout of School as Educational Media of Gender Equality for Young Generation - Karnita, Rosa; Satub, Nanda Pitria; Kusuma, Fitria Angga (Faculty of Engineering and Technology, Sampoerna University, 2023)
Gender is a concept that identifies differences between men and women. Along with social and cultural developments from time to time, gender limitations must not be complicated in carrying out work or activities. Both men and women can have rights and obligations regarding gender equality. However, Indonesia is still the lowest country viewing gender equality because patriarchal culture is still inherent in some circles of society. The role of the young generation is needed to increase awareness of gender equality in the modern era. The proximity of the young age to gadgets and technology makes webtoon a platform that can educate readers because it is easy to access and free of charge. The Pupus Putus Sekolah (Pupus Dropout) webtoon can be a medium for educating messages about gender equality through its characters, so it is hoped that awareness of gender equality will increase.